Analisis Preferensi Petani Terhadap Atribut Benih Kentang (G2) Industri di Kabupaten Garut - Noor, Trisna Insan; Rachmadi, Meddy; Deliana, Yosini; Tridakusumah, Achmad Choibar; Renaldy, Eddy; Indrawibawa, Diky (Universitas Galuh, 2024)
Potatoes or Solanum tuberosum L is one type of vegetable that is prioritized for development. The demand for potatoes also continues to increase from year to year. However, the dynamics of procurement of seed potato varieties are in fact only slightly adopted because they do not consider farmers' preferences and perceptions. This study aims to measure farmers' preferences for industrial seed potatoes in Garut Regency. This study used a quantitative method with a descriptive approach involving 100 respondents using conjoint analysis. The research locations were in two sub-districts in Garut Regency. The results of the study show that farmers' preferences for industrial potato seeds in Garut Regency lead to the subattribute of seeds free of plant disrupting organisms. Thus, these subattributes have the greatest influence on farmers' preferences in choosing industrial potato seeds. The need for assistance and empowerment of farmers from related parties in order to ensure the availability and affordability of certified superior potato seeds on the market.